2014
DOI: 10.1007/s11060-014-1374-9
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic significance of telomere maintenance mechanisms in pediatric high-grade gliomas

Abstract: Background Children with high-grade glioma, including diffuse intrinsic pontine glioma (DIPG), have a poor prognosis despite multimodal therapy. Identifying novel therapeutic targets is critical to improve their outcome. We evaluated prognostic roles of telomere maintenance mechanisms in children with HGG, including DIPG. Methods A multi-institutional retrospective study was conducted involving 50 flash-frozen HGG (35 non-brainstem; 15 DIPG) tumors from 45 children (30 non-brainstem; 15 DIPG). Telomerase act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 46 publications
2
37
0
Order By: Relevance
“…We have previously shown that over 73% of DIPG and 50% of high-grade gliomas (HGG; ref. 10) demonstrate telomerase activity. We recently conducted a molecular biology and phase II study of imetelstat, a potent inhibitor of telomerase (11,12), to estimate inhibition of tumor telomerase activity and efficacy in children with recurrent central nervous system (CNS) malignancies (13).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that over 73% of DIPG and 50% of high-grade gliomas (HGG; ref. 10) demonstrate telomerase activity. We recently conducted a molecular biology and phase II study of imetelstat, a potent inhibitor of telomerase (11,12), to estimate inhibition of tumor telomerase activity and efficacy in children with recurrent central nervous system (CNS) malignancies (13).…”
Section: Introductionmentioning
confidence: 99%
“…Telomerase activity has been detected in 10–100% of anaplastic astrocytomas [3, 4], 26–100% of glioblastoma [4] and 60–86% of ependymomas[5, 6]. High hTERT expression occurs in up to 76% of medulloblastoma/supratentorial primitive neuroectodermal tumors (PNET) [7] and 73% of diffuse intrinsic pontine gliomas (DIPG) [8]. Telomerase activation is a negative prognosticator across CNS tumors [9, 8, 5] and may play a role in cancer stemness [10, 5, 11], making telomerase inhibition a rational therapeutic target even in the setting of cancer recurrence and therapy resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies also found that the occurrence of TERT promoter mutations in gliomas was frequent [6,10,11]. So far, several studies on the association between TERT promoter mutations and prognosis of gliomas had been performed, but the conclusion still was not uncertain [6,[12][13][14][15][16]. The aim of the present meta-analysis was to assess the association between TERT promoter mutations and survival of glioma patients by pooling data from published studies.…”
Section: Introductionmentioning
confidence: 93%